TINJAUAN STATUS GIZI SISWA KELAS V SDN 002 PULAU BUSUK KABUPATEN KUANTAN SINGINGI - Taslim Taslim; Saripin Saripin; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
ABSTRACT, Inuman number of schools in the District, especially the poorer elementary students found a school that has a problem in student nutrition. It is known from the proficiency level of the student body posture. There are students who have a posture small, skinny, thin, tall, and too fat. This may be due to people's attention, parents on the nutritional status of students is very low. Schools rarely perform health activities on the nutritional status of students in the school. The low economic and parents make poor nutritional status of students rnenjadi, because weariness are adequately fed. Therefore, researchers wanted to find out by doing research on the nutritional status of students of SDN 002 Pulau Busuk. This type of research is descriptive with a sample of SDN 002 students in class V of 20 people with a total sampling technique. Data obtained from measurements of height and weight of students to determine the nutritional status of a sample of students. Data were analyzed using descriptive analysis. Based on data analysis is students who have normal nutrition only one person with 5 percentage remaining in the category of underweight weight level with a percentage of 95%. Therefore, based on the average score of the overall nutritional status of primary school students 002 Pulau Busuk District of Inuman categorized Less Good.Keywords : Nutrition Status